Nineteenth-Century Women's Travel Writings: A Case Study on Ana D'Almeida's Dairy and Chinese Women's Writing - Leong, Si Kei (University of Saint Joseph, 2011)
We live in an era in which critique of the West has become a deep-rooted phenomenon of the lives of non-Europeans. This paper contributes to the study of European women perception of South East Asia as mirrored in travel writing accounts and, independently but syncronic, of the Chinese women poets who wrote during a period a few decades before and after the mid nineteenth century. I shall be analysing the Western concept of femininity and domesticity in relation to and symultaneously attempting to reformulate Edward Said’s concept of Orientalism. Central to my research method is the fact that I am trying to add to to a traditional Western-oriented gender issues approach - baded on a review of the mid- nineteenth women travel writers - a reversed view, that being the representation of the Orient emerging from the vision of Chinese women literature. My research not only focuses on the literariness of travel writing, which has been widely neglected, but also on a vision of the Orient that is represented by some Chinese women writers in the nineteenth century –Gan Lirou 甘立媃 (1743-1819) and Lü Bicheng 呂碧城 (1883 – 1943). My research is not a survey study of Chinese literature, and it does not claim to be exhaustive. Instead, I attempt to systematize the problem of Western representations of the Orient by taking Ana d’Almeida’s diary, A Lady’s Visit to Manilla and Japan, as central reference and source of conceptual classification. From there, I am trying to further some gender issues drawn from Ana d'Almeida's text and identify symetric instances of those representations, if present, in Chinese literary texts written roughly in the same historical period. Expending Edward Said’s Orientalism, this paper tries to challenge the classic univocal Orient-Occident approach and to mirror Western Orientalist and pseudo- Orientalist ideas into contemporary Chinese writings. This is also meant to be an introduction to this cross-cultural comparative approach of feminity and domesticity open for further contributions in gender studies as well as in fields bordering social history, history of literature, literary theory and cultural anthropology
Keywords: Thesis and Dissertations PhD in History (D-HIS); University of Saint Joseph Thesis and Dissertations PhD in

Os Índios Potiguara: memória, asilo e poder - Simões, José Manuel (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Environmental Legacy of the Genocide: An Exploration into the Contamination Potential of Mass Grave Soils in Post-Genocide Rwanda - Amuno, Solomon; Tran, Emilie (University of Saint Joseph, 2013)
Keywords: Environmental; Genocide; Legacy; Rwanda

Rethinking special administrative regions Chinese cultural identities and the role of social media: a case study of Macau - Lou, Lai Chu (University of Saint Joseph, 2015)
Hong Kong and Macau were politically reunified with Mainland China in 1997 and 1999, respectively. These two cities culturally originated from Mainland China, but due to their own colonial experiences, the Chinese cultural identities within Hong Kong, Macau, and Mainland China became different. The nature of Chinese cultural identities within Hong Kong and Macau were hybridized, and they have formed their own Chinese cultural identities with their own peculiarities. The Internet is a popular communication medium and it facilitates cultural communication inside and outside of these three places. The high-speed development of modern technology leads to the variety of services that emerge in the Internet, such as discussion forum, Blog, Facebook, Twitter, etc. These new and open spaces serve as a platform for ordinary people to express themselves in different ways. General observations in the Internet reveal that the discussion on Chinese cultural identity among Hong Kong, Macau, and Mainland China exists. The combination of self-identity and reconstruction of self-cultural identity are happening in these differently colonized places. Some local Chinese people in Macau, and Taiwanese in Taiwan, share this kind of experience as well. Meanings in different issues via different symbols are formed and they can be seen from the photos that circulate in the Internet using threads posted in Blogs or discussion forums. All these kinds of images or contexts become symbols of recognizable identities. Internet use, therefore, has facilitated the cultural communication between Hong Kong, Macau, Mainland China, and Taiwan. It has also intensified the enlightenment of Chinese cultural identity, showing and highlighting in effect the remnants of recognizable traits in these territories that were once colonized by different states. In essence, they may arguably have formed heterogeneous Chinese cultural identities. This study presents the uniqueness of the formation of Macau identity in comparison to Hong Kong, and how different it was from Hong Kong after the end of the colonial period. This ‘awakening process’, it is argued, provides a new perspective for understanding the attendant connotations and evaluations of cultural identities, and the different perspectives used to understand how the Internet is reshaping the social world. The reconstruction of cultural identity is a global issue and cultural hybridity is an essential element for reconstruction of self-cultural identity in the postcolonial period. This study employs postcolonial theory, along with observation, in-depth interview and online data collection and content analysis that were adapted during the course of the research, in order to discuss this phenomenon
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Migrant transnationalism and religious transformation: religious faith and practice among Filipino migrants (An Anthroplogical Approach Focusing on Macau) - Alabanza, Ian Shelley Sasha Pugal (University of Saint Joseph, 2016)
Religion and migration are both phenomena that have endured perennially in the experience of humanity. However, studies on the relationship of these two subjects are not as prevalent compared to how widespread international migration has become especially among people coming from religious societies. This work contributes to the knowledge base on the significance of religion within the context of international migration by looking at how religious faith and practice evolve as a result of the experience of migration. Interviews about the migration narratives of Filipino Catholics working in Macau were conducted. These were supported by data collected through the use of survey questionnaires that look into changes in religious practices of respondents as well as their attitudes towards faith and belief. The study has found that there is constancy in the religious faith and practice of Filipino Catholics even amidst external changes to the physical and social environment brought about by moving to a predominantly secular society. Through recourse to anthropological analysis, this immutability of faith is attributable to the unique ethnographic feature of Filipinos’ high regard for the centrality and importance of interiority in their life. Keywords: migration, immigrant religion, faith, Filipino religiosity
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Macau fashion industry in the 21st Century: a global studies perspective on Asia-Europe cultural exchange - Dias Cardoso, Ana Cláduia (University of Saint Joseph, 2017)
Macau is a dynamic city with a unique blend of Eastern and Western cultures, which has become a well-known travel destination. Macau is not only home to the casinos, but also a shopping paradise, where we can find international luxury brands and local designer brands. The local fashion industry has a strong follower base, taking a different route than that of the Textile and Garment Industry in the 1980s. Nowadays, the local Fashion Industry is not only focused on production, but more on the design and creativity. Macau is a city rooted in the casino industry, having shifted from an industrial economy into a service-based one. This study aims to assess the relations between Asia and Europe with regard to their impact on the creative process of local fashion designers, to understand how local designers balance between market, creativity and aesthetics. Also, it is important to understand how Macau government supports local brands such as: “Made in Macau”. In order to accomplish our goal, several academic areas will be addressed, such as fashion design and the cultural and creative industries in their broad sense, (aesthetics, history, creativity, identity, economy, ergonomics, cognition, and social value). A mix of quantitative and qualitative methods have been used, including questionnaires, open-ended interviews, case-study research, ethnographic methods, historical research and visual methodologies. In the following chapters, this studies will describe mainly the Macau fashion industry in a globalized era and the multiculturalism’s influence on the local fashion designer’s collections
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; Thesis and Dissertations PhD in Global Studies (D-GLS); University of Saint Joseph

Ambivalence, relationality, complexity and integration grassroots artistic landscape of Macao S.A.R in the post-retrocession era - Mendes, Carla de Utra (University of Saint Joseph, 2017)
This research intends to analyze how the social, political, economical and cultural transformations of the retrocession of Macao S.A.R. to China influenced the contemporary grassroots artistic production, namely their response to the issue of One Country, Two Systems policy. This transitional state of these places in-between creates a somehow ambivalent situation where some of the core values of identity and heritage are fading away due to the forces of the current development. In this sense, it urges to consider the ways in which artists in the post-retrocession era in their lived experiences, form their own sense of community and consciousness of place, time and belonging and, by doing so, can contribute to the preservation of some of the local and specific characteristics, enhancing the cultural vitality of the region. The growing interest by the artists in the issues of preservation and engagement with the locality, trough memory and history, manifested in ‘alternative’ modes of production, is providing a different model of ‘place making’ and a narrative that contrasts and complements some of the top-down cultural policies. Since the focus of development in these territories has been on the idea of creative industries, entertainment and tourism as possible realities for the pressing economical diversification, these grassroots models, functioning as the ‘second system’ open up complexity, providing different questions and answers to the future of artistic production. Finally, departing from these examples, we analyze the possibility of a new image for these kinds of artistic practices, through their incorporation into the possibility of relational aesthetics ‘with Chinese characteristics’, within the perspective of integration, and as emergent features in the field of contemporary art
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Child protection during emergencies in Fiji and Tonga: enabling, constraining or controlling children's agency and participation - Stuebing, Dennis L. (University of Saint Joseph, 2017)
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

Semiotic multimodality :a filmic analysis of Wong Kar-Wai's in the mood for love / - Tan, Chee Seng (University of Saint Joseph, 2017)
The study builts on Bateman and Schmidt’s (2011) and Tseng’s (2009) research on film as a form of “cinematographic document,” and continues their efforts to construct a semiotic mode of film. The author recognizes the complexity of undertaking research in the domain of semiotic discourse. This study argues that as film analysis is about ways of seeing and synthesizing different cinematic styles, strategies; learnt cinematic conventions and reflective viewing is imperative. The interaction of robust multimodal resources, well-defined analytic units, based on dependable models, and conducted through a discursive process should align to produce fruitful filmic discourse. The study premised on the assumption that film is more than a “self-enclosed signification system” but a crucial “cultural practice” that “reflect and inflect culture.” Taken together, this view underscores the importance and interactivity of cinema, culture and society. To this end, the study contributes to filmic meaning making, the New Hong Kong Cinema, and finally, the present study invariably serves as a form of “social document” or “cultural artifacts” in its exploration of Hong Kong ever changing identity, culture and moods.
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph

From digital to Facebook divide: social capital benefits for Facebook immigrant - Yung, Chun Sing (University of Saint Joseph, 2018)
Two billion users make Facebook of academic interest. This thesis creates a Facebook Divide Index, the delineated categories of Facebook Native, Facebook Immigrant, and Facebook Isolate, and develops Facebook inequality concepts. Macau has a fast- growing number of Facebook Immigrants who benefit from using the online social network. Data from participation-observation and surveys demonstrate social capital gain by Facebook Immigrants, with older generation Facebook users relatively happier than their younger counterparts. The thesis concludes that society needs to equip and empower the older generation or Facebook Isolates, so that they can benefit from online social network usage
Keywords: PhD in Global Studies (D-GLS); Thesis and Dissertations; University of Saint Joseph